Loop stability analysis of boost circuit under globally dynamic compensation strategy. Issue 16 (24th January 2019) - Wang, Xiaofan; Guo, Yingna; Cheng, Weibin; Leng, Mingquan
Abstract : The PFC Boost converter controlled by the mode of CCM has strong non‐linearity due to the use of non‐linear elements such as power switch and multipliers. Here, a globally optimised control strategy of dynamic slope compensation is proposed to eliminate bifurcation, chaos behaviours. Time‐varying adjustment of control efforts can achieve the optimal compensation within each switching cycle. First, the model and the system transfer function of the circuit controlled by the global dynamic slope compensation control mode have been derived and the stability of the system is analysed from the frequency domain at the same time. The voltage outer loop is used to compensate the worst‐stability zero‐crossing time, which ensures that the circuit meets the frequency domain stability requirements throughout the whole cycle. Finally, the experimental circuit has been built to verify the theory, it can be found that the theory has good prospects in practical application and promotion through comparison between the simulation and the measured circuit waveforms.